A Proposed Project of Disposable Facemask as Alternative Home Slippers: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Everyone’s life is affected by COVID-19, regardless of their wealth, age, or stage of life.However, the disposable facemasks we wear every day that are thrown away into the road orthe ocean due to poor waste management also have an impact on the environment.Therefore, in this study, we transform garbage into something beneficial that is also safe forthe environment.Our results showed that there was no significant difference in the level of acceptability ofdisposable face masks as alternative home slippers between the STEM teachers and Grade-12 STEM students. Despite the challenges we faced in obtaining an adequate supply ofdisposable face masks and ensuring their proper disinfection and sterilization, we were able toimplement solutions such as placing a trash box for used face masks and implementingstringent disinfection protocols. These findings provide valuable insights into the acceptabilityof disposable face masks as alternative home slippers and highlight the importance of properdisinfection and sterilization practices to minimize the risk of COVID-19 transmission.For further enhancement and improvement of the study, the ensuing discussions and therecommendations proposed are as follows: to enhance the comfort and appearance; refer todifferent studies to improve this research; add new size and color; to improve the quality of thehome slippers, this project intends to investigate the idea of recycling disposable facemask asan alternative home slipper.
Keywords: Engineering